Shared vision-based teamwork cohesiveness: catalyst for organizational commitment and organizational citizenship behavior (self congruence theory perspective) - Muhammad Risal Tawil; Ahmad Amiruddin; Yohanis Rongre; Sudirman Sudirman; Abdul Malik (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The study reviews the important role of Shared Vision-Based Teamwork Cohesiveness (SVBTC) in bridging Organizational Commitment (OC) and Organizational Citizenship Behavior (OCB) in employees of an organization. One of the positive behaviors that are expected to grow in an organization is the presence of high OC and OCB in employees. This study confirms that employees who have good OC are not always supported by good OCB through a review of various previous studies. In this study, a catalyst in the form of Shared Vision-Based Teamwork Cohesiveness (SVBTC) is presented from the point of view of Self Congruence Theory (SCT) which is believed to strengthen the relationship between OC and OCB. Applying for a literature review, this study provides a new perspective on the factors that can increase OCB for employees in an organization.